DAMPAK PERUBAHAN BUDAYA DI DAERAH KABUPATEN BUTON TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Nadila; Marna; Ayu Syukur; Mustar; Dian Lestari; Haliadi (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the significant impact of cultural changes occurring in Buton Regency on the learning process at the elementary school level. The main issue raised is the shift in local wisdom values, such as the tradition of politeness (poma-maa-maa) and the use of regional languages, which are starting to be eroded by modernization and the use of digital technology by students in the school environment. The method used in this study is descriptive qualitative with data collection techniques through participatory observation, in-depth interviews with teachers and traditional leaders, and a study of local content curriculum documents. The results show that cultural changes have an impact on the decline of discipline based on local values ​​and a significant reduction in students' understanding of their own cultural identity. However, on the other hand, this change opens up opportunities for the integration of more dynamic digital-based learning media if managed properly. In conclusion, a reconstruction of the local content curriculum is needed that can align technological advances with the preservation of Buton's noble values ​​for the development of educational knowledge and practice.